Government initiatives for empowerment of Indian Poultry sector - Kumar, Vijay; Rao, S V Rama; Mahesh, P S (Indian Farming, 2024)
The Central Government support in poultry sector can be categorized into four sections viz. Capacity development, Input and service support, Financial support and Policy issues. There are four Central Poultry Development Organizations (CPDO) in addition to National Institute of Agricultural Extension Management (MANAGE), network of 731 Krishi Vigyan Kendra (KVK), Centre of Excellence for Animal Husbandry (CEAH) and several institutes of Indian Council of Agricultural Research (ICAR) are engaged in capacity building as well as input and service to stakeholders. National Livestock Mission (NLM), Animal Husbandry Infrastructure Development Fund (AHIDF), National Bank for Agriculture and Rural Development (NABARD) and many more schemes extend financial support to the sector. Government is also making policy for trade, health and welfare, contract farming guidelines etc.